Influência do plasma rico em plaquetas derivado do aspirado de medula óssea na cicatrização de defeitos periodontais: estudo histológico, histométrico e imunoistoquímico em ratos - Campos, Natália de [UNESP] (2014)
This study evaluated the influence of platelet-rich plasma derived from bone marrow aspirate (PRP-bma) on the healing of periodontal fenestration defects (PFD) in rats. PFD were surgically created in the mandible of 40 rats. The animals were randomly divided into 2 groups: C and PRP-bma - defects were filled with blood clot or PRP-bma, respectively. Animals were euthanized at either 10 or 30 days post-operative. Histologic, histometric and immunohistochemical analyses were performed. Percentage of new bone (NB), density of newly formed bone (DNB), new cementum (NC) and extension of remaining defect (ERD) were histometrically evaluated. Proliferating cell nuclear antigen (PCNA), bone sialoprotein (BSP), osteocalcin (OCN), and tartrate-resistant acid phosphatase (TRAP) immunohistochemical staining were performed. Immunolabeled cells were quantified. Data were statistically analyzed (ANOVA; Tukey, P < 0.05). At 10 days, groups C and PRP-bma presented similar amounts of NB and DNB, NC formation was not observed. At 30 days, groups C and PRP-bma presented similar amounts of NB and DNB; Group PRP-bma showed significant NC formation, with collagen fibers inserted obliquely or perpendicularly to the root surface, while NC formation was not observed in any Group C specimen. Group PRP-bma presented a significantly higher number of PCNA-positive (at 10 days) and BSP-positive cells (at 10 and 30 days) than Group C. No significant differences in the number of either OCN-positive or TRAP-positive cells were observed between groups at 10 or 30 days. It can be concluded that PRP-bma promoted NC formation with a functional periodontal ligament